2018
DOI: 10.1002/hep4.1285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonalcoholic Fatty Liver Disease in the Female Population

Abstract: There is a paucity of recent data about the epidemiology and long‐term outcomes of nonalcoholic fatty liver disease (NAFLD) in the female population. Our aim was to assess the prevalence, risk factors, and mortality of NAFLD in female adults of the United States. Data from the National Health and Nutrition Examination Survey (NHANES) III and NHANES 1999‐2014 were used. NAFLD status was determined by the U.S. Fatty Liver Index (US‐FLI) in the absence of other liver diseases and excessive alcohol consumption. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Such a finding confirms another report that also found the mortality rate is increasing among women with NAFLD . However, our study furthers this knowledge and notes that women encounter more deaths from cirrhosis when compared with men, suggestive that many women may have NASH rather than just NAFLD . Furthermore, our work highlights that there is possibly a sex bias when diagnosing NAFLD and that attention should be directed toward educating the public and health care workers that women are at risk for NAFLD and its negative outcomes, including patient‐reported outcomes and NAFLD‐related mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such a finding confirms another report that also found the mortality rate is increasing among women with NAFLD . However, our study furthers this knowledge and notes that women encounter more deaths from cirrhosis when compared with men, suggestive that many women may have NASH rather than just NAFLD . Furthermore, our work highlights that there is possibly a sex bias when diagnosing NAFLD and that attention should be directed toward educating the public and health care workers that women are at risk for NAFLD and its negative outcomes, including patient‐reported outcomes and NAFLD‐related mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Also of importance is that the death rate for adults with NAFLD is increasing significantly more in women than men . Such a finding confirms another report that also found the mortality rate is increasing among women with NAFLD . However, our study furthers this knowledge and notes that women encounter more deaths from cirrhosis when compared with men, suggestive that many women may have NASH rather than just NAFLD .…”
Section: Discussionsupporting
confidence: 88%
“…(9) Similarly, a study using NHANES III and NHANES 1999-2014 data found that risk of 5-year mortality was higher among women with NAFLD compared to women without NAFLD. (34) Although NAFLD is more common among men, risk and progression from simple steatosis to NASH has been suggested to increase among women after menopause. (35)(36)(37)(38)(39) In the current study, however, prevalence of NASH among women aged ≥55 years (3.3%) was similar to that of women aged <55 years (3.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Among the liver disorders, NAFLD is considered the most common disease [49][50][51] . Indeed, NAFLD is the commonest cause for liver dysfunction in our study cohort, with 4.2% of the pregnant women being diagnosed with NAFLD.…”
Section: Discussionmentioning
confidence: 99%